The Relationship between Socioeconomic Status and White Water Rafting Sports Participation - Riyana, Ardi; Syamsudar, Bangbang; Lutan, Rusli; Karisman, Vicki Ahmad (Journal of Physical and Outdoor Education, 2024)
Sports tourism is a combination of tourism and sports. Sports tourism is one type of tourism activity that is developing quite rapidly because Indonesia has vast mountains, oceans, rivers and lakes. One of them is through the use of nature from rivers, namely the sport of white water rafting which is in great demand by tourists, which of course will have an impact on the economic conditions of local tourist attractions. The United Nations World Tourism Organizations (UNWTO) explains that sports tourism is the fastest growing tourism sector, in this sector many tourists are interested in sports activities. So it will produce large economic value. From the above background, the author is interested in researching the income level of tourists who participate in white water rafting. This research aims to determine the relationship between socio-economic status/income level (X) and white water rafting participation (Y). In order to achieve the research objectives, intervening variables are needed, namely: the attractiveness of white water rafting, the intensity of white water rafting sports activities, the enjoyment of white water rafting sports, activities of obtaining information through print media, activities of obtaining information through electronic media/TV, and personal development. The research sample used the Accidental Sampling or Convenience Sampling technique as many as 73 white water rafting athletes. The research instrument uses a questionnaire. Data analysis uses the chi square technique or also called chi square. Based on the results of the chi square test recapitulation above, it can be seen that the p-value is 0.001. Because the p-value is smaller than 0.05, it means that there is a significant relationship between socio-economic status/income level and frequency of participation. Conclusion: there is a relationship between socioeconomic status/income level (X) and frequency of participation in white water rafting (Y).